Effects of Arsenic on Nutrients Uptake of Wheat (Triticum aestivum L) at Different Growth Stages - Liu, Quanji; Zheng, Chuangmu; Hu, Chengxiao; Tan, Qiling; Sun, Xuecheng (Asian Journal of Chemistry, 2011)
Arsenic (As) levels in soils have been elevated, especially in some wheat-producing areas of China. Understanding the effects of arsenic pollution on wheat (Triticum aestivum L) nutrient elements is of major significance for food production and security. A soil pot experiment was carried out to study the uptake of nutrient elements and arsenic at different growth stages. Arsenic concentrations in wheat shoots is ear sprouting stage > jointing stage > tillering stage. Ear sprouting stage was the main stage that arsenic could affect the nutrient elements uptake. When arsenic concentration in soil was £ 60 mg/kg, arsenic increased the straw P, N and K concentrations at the jointing and ear sprouting stages and enhanced the biomass as well as other agronomic parameters such as grain yield. The increase in wheat biomass and yield probably resulted from P, N, K abundance. However, when soil arsenic was ³ 80 mg/kg, arsenic significantly decreased macroelement (P, K and N) concentrations in the shoots. The reduction in wheat biomass and yield at high arsenic levels probably resulted from both arsenic phytotoxicity and nutrient elements lack. The relationship between shoots arsenic and shoots N, P, K concentrations was quadratic equations. The Cu, Fe, Zn concentrations in wheat shoots significantly were decreased and they were negatively linearly correlated with arsenic concentrations in wheat shoots (R2 = 0.7064, 0.8265 and 0.8302, respectively). The highest arsenic concentration in wheat grains was 0.39 mg/kg and did not exceed the maximum permissible limit for food stuffs of 0.7 mg/kg.